(untitled) (Altre Modernità, 2014)
Following a brief introduction to the existing research on Vicki Baum (1888-1960) and her work, this study examines the importance of assimilation, identity, and self-discovery both in the author’s biography and in her narrative. The analysis of Menschen im Hotel (1929) and Hotel Berlin (1943/44) collocates the fictional conflicts between modernizing inputs and traditional settings, between self-deception and ethical responsibility within the wider field of Baum’s experience as an assimilated Jew first in the Weimar Republic and then, after the so-called voluntary exile, in the U.S. Even though the writer herself was not willing to stress her Jewishness, this article contends that Vicki Baum’s Jewish background and her ability to absorb every cultural ambience are crucial for the understanding of her texts.